Ambiguous avant-gardes and their geographies: on blank spots of the postgrowth debate - Lange, Bastian; Bürkner, Hans-Joachim (DIE ERDE – Journal of the Geographical Society of Berlin, 2021)
In the following article, the focus is on the transformative potentials created by so-called persistence avant-gardes and prevention innovators. The text extends Blühdorn’s guiding concept of narratives of hope (Blühdorn 2017; Blühdorn and Butzlaff 2019) by considering those groups that are marginalized within debates on socio-ecological transformation. With a closer look at the narratives of prevention and blockade that these actors engage, the ambiguous nature of postgrowth avant-gardes is carved out. Their discursive, argumentative, and effective inhibition of transitory policies is interpreted as a pro-active potential, rather than a mere obstacle to socio-ecological transformation. Adding a geographical perspective, the paper pleads for a more precise theoretical penetration of the ambivalent figure of avant-gardes when analyzing processes of local and regional postgrowth.